FORMASI KEBUTUHAN PEGAWAI DALAM PENERIMAAN CALON PEGAWAI NEGERI SIPIL (CPNS) BADAN KEPEGAWAIAN DAERAH KOTA MAKASSAR - Auliya Citra R; Muh Yunus (fakultas Ushuluddin dan Dakwah IAIN Bone, 2020)
The aim of this research was to clescribe how the formation needs of servant inacceptance prospective civil servant like BKD Kota Makassar. This research was about adescriptive qualitative research. The data sourched by primer and sekunder data. Thedata was collected through observation and statement analysis. The observation was usedto analysis qualitative data through technique analysis and statement analysis was takenfrom the result of interviewing informan and endorsement data intensively. The finding ofthis research showed that the servant need was not enough. It based on from position andjob’s formation where the appropriate competence. Level toward apparatus position isnot agree with conditions.Keywords: formation, supplies, officer in acceptance CPNS